LATERAL PERIODONTAL CYST: A CASE REPORT (International Journal of Food and Nutritional Sciences, 2022)
As per the sparse literature, a cystic lesion that grows on the lateral surface of the erupted vital teeth is called as lateral periodontal cyst. This type of cyst is one of the most uncommon developmental odontogenic cysts with an incidence of 0.4% of all odontogenic cysts and 0.7% of all the cysts of the jaw. In this article we report a case of 19 year old female who came to the to the Department of Oral and Maxillofacial Surgery, Santosh Dental College and Hospital with the chief complaint of swelling on the right side of the face. The swelling was asymptomatic but was prominently evident extraorally on the right side of the face. Surprisingly, on histopathological examination the lesion came out to be lateral periodontal cyst. Any lesion which appears radiolucent in the radiograph with round or oval well circumscribed border adjacent to the roots of vital teeth can be suspected with lateral periodontal cysts.